Geospatial technology in soil resource inventory and land capability assessment for sustainable development – Wayanad district, Kerala - KUMAR, Y. SURESH; GAHLOD, N. S.; ARYA, V. S. (Journal of Soil and Water Conservation, 2020)
Geospatial technology has opened new vistas for natural resources mapping and their management. It has been widely used for soil resources inventory and generation of spatial and temporal information for sustainable landuse plan at a specific scale. The present study was undertaken to identify the different physiographic situations, landforms and soil resources to assess the chemical and physical inherent soil properties, topography, slope, climate and land use as an external land feature. IRS-ID (LISS-III) satellite data was used to delineate different physiographic units using image interpretation keys on 1:50,000 scale alongwith exhaustive ground truthing. The soils were classified on the basis of Soil survey and laboratory data. The generated spatial and non-spatial data was integrated in the Geographic Information System (GIS) environment and various thematic layers were derived to prepare land capability map of the district. The main physiographic units identified in the study area were undifferentiated hill slopes, pediments, pediplains and narrow river valleys. The soils found in the area were moderately deep to deep, fine loamy to fine textured on hill side slopes occupying 71.6% area, deep to very deep, fine loamy to fine textured on pediments covering 7.8% area and very deep, fine to coarse loamy soils, mostly aquic in nature in narrow river valleys with 19.3% area of district and classified as Entisols, Inceptisols and Mollisols. It was found that soils of the valley fall in land capability class- II, pediments in class- III and hills in the range of IV to VIII.